2023
DOI: 10.1002/adem.202201425
|View full text |Cite
|
Sign up to set email alerts
|

High Gravimetric Capacitance MXene Supercapacitor Electrode Based on Etched Ti3C2Tx by Chemical Etching

Abstract: Ti3C2T x MXene is one of the most promising electrode materials for supercapacitors, but it often suffers in poor experiment gravimetric capacitance, which limits practical applications in industry needs. Herein, etched Ti3C2T x MXene with high gravimetric capacitance is prepared by chemical etching of MXene with concentrated alkaline solution. The intercalation of K+ and the scissor role of OH− can simultaneously enlarge the interlayer spacing and cut the size of sheets, which lead to the high active‐site c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The etching reaction in an alkaline solution leads to an increase in interlayer spacing and a size reduction, which causes an increase in the active sites of Ti 3 C 2 T x MXene and enhancement in cation diffusion. As a result, the e-Ti 3 C 2 T x MXene can attain a gravimetric capacitance of 368.1 F/g at a current density of 2 A/g …”
Section: Synthesis Of Mxenementioning
confidence: 99%
See 3 more Smart Citations
“…The etching reaction in an alkaline solution leads to an increase in interlayer spacing and a size reduction, which causes an increase in the active sites of Ti 3 C 2 T x MXene and enhancement in cation diffusion. As a result, the e-Ti 3 C 2 T x MXene can attain a gravimetric capacitance of 368.1 F/g at a current density of 2 A/g …”
Section: Synthesis Of Mxenementioning
confidence: 99%
“…Compared to pure MXene films, MXene/V 2 O 5 films’ flexibility and electrochemical capabilities are improved. The electrode also has better specific capacitance and cycling stability . Rakhi et al reported for the first time that depositing ε-MnO 2 whiskers on the surface of MXene to form electrodes for aqueous pseudocapacitors with increased surface area improved electrochemical performances in an aqueous electrolyte .…”
Section: Mxene-based Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,13] Besides, MXene demonstrates excellent electrical conductivity, [14,15] thermal conductivity, [15][16][17] nontoxicity, [18] stiffness, [19] surface chemistry, [20][21][22][23] and mechanical properties. [24,25] Because of these properties, MXene has been widely utilized in flexible electrodes, [26,27] capacitors, [28,29] electromagnetic interference shielding (EMIS) materials, [14,30,31] biomedical devices, [2,32] environmental protecting films, [33] and photothermal and electrothermal converting materials. [34][35][36] In addition, MXene has been introduced to elastomers such as natural rubber (NR), [37] acrylonitrile butadiene rubber (NBR), [38] and styrene-butadiene rubber (SBR) [39] as a mechanical reinforcement.…”
Section: Introductionmentioning
confidence: 99%